Enhancing Self-Determination for Students with Complex Communication Needs using the Self-Determined Learning Model of Instruction - Raley, Sheida K.; Shogren, Karrie A.; Burke, Kathryn M. (Journal of the American Academy of Special Education Professionals, 2021)
Supporting the development of skills associated with self-determination (e.g., goal setting and attainment, problem solving) and providing opportunities to practice those skills impacts valued school and postschool outcomes of students with complex communication needs. To address this need, the Self-Determined Learning Model of Instruction (SDLMI) is designed to enable practitioners (including those with special education expertise) to teach students to self-regulate goal setting and attainment processes and self-direct their learning to achieve meaningful goals. When using the SDLMI with students with complex communication needs, there are specific supports that are particularly useful; therefore, this manuscript describes strategies that practitioners can use when implementing the SDLMI with students with complex communication needs to enhance overall self-determination and positive postschool outcomes and provides guidance for the inclusion of students with complex communication needs in self-determination research.